(untitled) (mathematica didactica, 2004)
The contribution begins by giving a survey on evaluative reports on multi-medial learning in mathematics instruction at the school and at the teacher college and university levels. The standardized presentation structured according to the categories of acceptance, as well as to those of process, effect, and efficiency of learning, permits to compare the various approaches, and to identify the basic patterns of research. The ensuing discussion of the evaluation within the MaDiN project leads towards extending the range of aspects of research methodology. The results are requirements concerning the evaluation of multi-medial learning in mathematics education presented in the form of theses.